Postero-medial elbow problems in the adult athlete - Eygendaal, D.; Safran, M. R. (British Journal of Sports Medicine, 2006)
The ligamentous, osseous, musculotendinous, and neural structures at the postero-medial side of the elbow are at risk for various injuries in overhead athletes. The combination of valgus and extension overload during overhead activities results in tensile forces along the medial stabilising structures, with compression on the lateral compartment and shear stress posteriorly. The combination of tensile forces medially and shear forces posteriorly can result in ulnar collateral ligament (UCL) tears, flexor-pronator mass injuries, neuritis of the ulnar nerve, posterior impingement, and olecranon stress fractures. Most symptomatic conditions of the overhead athlete can be treated conservatively initially. In cases where conservative treatment is unsuccessful surgical intervention is indicated. Recent advances in arthroscopic surgical techniques and ligamentous reconstruction ensure that the prognosis for return to pre-injury level is good.